ETHNOMEDICINAL USES OF PTERIDOPHYTES OF TIKRI FOREST, GONDA, UTTAR PRADESH - SHOBHIT KUMAR SRIVASTAVA,; RAVI PRATAP GAUTAM,; SHASHANK KUMAR SINGH,; S. DOMINIC RAJKUMAR, (International Journal of Pharma and Bio Sciences, 2015)
The Pteridophytes are considered to be one of the primitive groups in vascular plants which are scattered all over the world. More than 1200 species of fern & fern allies have been reported from India. Being a group of lower plants, they were always uncared for and their valuable aspect has been ignored. Very less attention has been given towards the utility of Pteridophytes though they possess economic importance and medicinal value. The ferns are also recorded as valuable drug yielding plants. This paper deals with the ethnomedicinal usage of ferns in the treatment of different types of diseases. In this paper the botanical name, family & ethnomedicinal uses are provided.